2014
DOI: 10.1371/journal.pone.0102438
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 Induces Major Energetic Metabolism Reprogramming in Breast Cancer Cells

Abstract: The hypermetabolic nature of cancer cells and their increased reliance on “aerobic glycolysis”, as originally described by Otto Warburg and colleagues, are considered metabolic hallmarks of cancer cells. BRCA1 is a major tumor suppressor in breast cancer and it was implicated in numerous pathways resulting in anticarcinogenic functions. The objective of our study was to address specific contributions of BRCA1 to the metabolic features of cancer cells, including the so-called “Warburg effect”. To get a comprehe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(60 citation statements)
references
References 44 publications
1
57
0
Order By: Relevance
“…Moreover, a high percentage of individuals harboring defects (mutations or deletions) in the tumor suppressor gene BRCA1 have receptor triple negative tumors and are at an increased lifetime risk for developing high aggressive breast tumors [62,63]. Interestingly, it has been suggested that BRCA1, a nuclear DNA damage response protein, similar to ATM, is involved in mtDNA maintenance, mtDNA integrity and mtDNA damage repair and regulates cellular metabolism [64]. Our analysis of the TCGA dataset suggests that tumors containing low mtDNA content harbor a higher frequency of pathogenic BRCA1 mutations (Suppl.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a high percentage of individuals harboring defects (mutations or deletions) in the tumor suppressor gene BRCA1 have receptor triple negative tumors and are at an increased lifetime risk for developing high aggressive breast tumors [62,63]. Interestingly, it has been suggested that BRCA1, a nuclear DNA damage response protein, similar to ATM, is involved in mtDNA maintenance, mtDNA integrity and mtDNA damage repair and regulates cellular metabolism [64]. Our analysis of the TCGA dataset suggests that tumors containing low mtDNA content harbor a higher frequency of pathogenic BRCA1 mutations (Suppl.…”
Section: Discussionmentioning
confidence: 99%
“…BRCA1 contributes to various metabolic modifications in cancer cells including inhibition of glycolysis and activation of TCA cycle and oxidative phosphorylation (94). BRCA1 is also known to inhibit energy-consuming anabolic processes such as lipid biosynthesis in cancer cells by interacting with the phosphorylated form of acetyl coenzyme A carboxylase alpha (ACCA), the rate-limiting enzyme that catalyzes de novo fatty acid biogenesis (95).…”
Section: Mutational Control Of Metabolic Regulationsmentioning
confidence: 99%
“…It is worth noting, the evidence suggesting that DBS repair pathways are developmentally regulated with HR being crucial in embryonal cells and NHEJ during cell cycles of differentiated cells. DBS repair by HR in primary somatic Recent metabolomics and transcriptomic data further suggests that BRCA1 can cause reversion of aerobic glycolysis (known as a Warburg effect) in breast cancer cells [81].…”
Section: Brca1 In Dna Damage Responsementioning
confidence: 99%